Is Monkeypox a Concern in Multiple Sclerosis Patients? A Letter to Editor - Asadollahzadeh, Elnaz; Ghadiri , Fereshteh; Ebadi , Zahra; Naser Moghadasi, Abdorreza (Archives of Academic Emergency Medicine, 2022)
Individuals with autoimmune conditions have been characterized as the population very much prone to illness. This is because of the way various diseases impact their immune system, and because immunosuppressant medications were employed to cure the majority of these ailments (1). By weakening the immune system, these drugs allow the control of many autoimmune disorders such as multiple sclerosis. Patients with multiple sclerosis who use these drugs are in danger of developing a weak immune system and a wide range of infectious diseases such as herpesvirus infections (2). Viral, bacterial, and fungal infections can cause MS exacerbations (3).